Perception and awareness of unintentional childhood injuries among primary caregivers of children in Vellore, South India: a community-based cross-sectional study using photo-elicitation method - Leeberk Raja Inbaraj; Kulandaipalayam Natarajan Sindhu; Lalmalsawmi Ralte; Basir Ahmed; Chandni Chandramouli; Elza Rebecca Kharsyntiew; Evelina Jane; Joshaphine Victoria Paripooranam; Nikhil Muduli; Padebettu Devendra Akhilesh; Prakash Joseph; Renata Nappoly; et al. (BMC, 2020)
Abstract Objective We studied the primary caregivers' perception, and further, their awareness of unintentional childhood injuries in south India. Methods A cross-sectional study was conducted in the rural block of Kaniyambadi, Vellore, among 300 primary caregivers of children aged between 0 and 14 years. A semi-structured interview was conducted with the primary caregivers using a photo-elicitation method, with a visual depiction of ten injury risky scenarios for a child. Scoring was done to assess the perception of environmental hazards in these scenarios, and further, knowledge on the prevention of these injuries. An independent 't' test was done to elicit differences in mean scores and a multivariate regression analysis was applied to ascertain factors independently associated with the scores. Results Primary caregivers had adequate perception regarding risks posed to children in scenarios such as climbing trees (96.2%), playing near construction sites (96%), firecrackers (96.4%) and crossing unmanned roads with no traffic signals (94%). Knowledge of prevention was poor however, in the following scenarios: a woman riding a bicycle without safety features, with child pillion sitting behind bare foot and legs hanging by one side (72.6%); a child playing near a construction site (85.9%); and a child playing with plastic bags (88.3%). Overall, educational status of the primary caregiver and socioeconomic status were associated with poorer perception of risks and knowledge about unintentional childhood injuries and their prevention. Conclusions Pragmatic community-based childhood interventions incorporated into existing programs, with a special focus on road traffic injuries, burns and suffocation need to be implemented in high-risk settings of rural populations in South India.